Intertextual References to the Story of A. K. Doyle “A Study in Scarlet” in Modern Literature (N. Gaiman “A Study in Emerald” and Ya. Wagner “A Study in Purple”) - Yu. A. Gimranova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The intertextual layers of the stories by N. Gaiman “A Study in Emerald” and Ya. Wagner “A Study in Purple” are examined in this article. It is shown in the article that the intertextual fields of modern texts are allusions, reminiscences, metatextuality, paratextuality, architextuality, as well as onomastic quotations. It is concluded that  the images and motives of the classic detective work of the early XX century create a visible intertext in the works of the XXI century and become a central device that generates secondary artistic worlds. It is emphasized that contextual correlation with A. K. Doyle’s story allows modern writers (both English-speaking and Russian-speaking) to create clear projections to the text about the famous detective, expanding the chronotopic organization of their metatexts. Particular attention is paid to the comparative intertextual analysis of the classical text of Arthur Conan Doyle with the stories of modern writers — English (N. Gaiman) and Russian (Ya. Wagner). The novelty of the research is seen in the insufficient appeal of literary science and literary criticism to the analysis of Doyle’s intertextuality and intertextual references to the story “A Study in Scarlet”, in particular. The relevance  of the study is also due to the enduring reader’s interest in the detective genre and in the work of Arthur Conan Doyle.